Molecular identification and characterization of Maconellicoccus multipori (Takahashi) (Hemiptera: Pseudococcidae) on Piper nigrum L. - Tri Lestari Mardiningsih; Dewi Sartiami; Miftakhurohmah Miftakhurohmah; Setyowati Retno Djiwanti; Rohimatun Rohimatun; Siti Hardiyanti; Rubi Heryanto; Widi Amaria; Suwarti Suwarti (Universitas Lampung, 2025)
The mealybug Maconellicoccus multipori (Takahashi) was identified on black pepper (Piper nigrum L.) seedlings in a greenhouse in Bogor, West Java, using both molecular and morphological characterization. Two mealybug isolates were successfully amplified with primer pairs targeting the LCO region of the mitochondrial cytochrome oxidase I (COI) gene, yielding a 491 bp PCR product. The nucleotide sequences of both isolates (GenBank accession numbers LC666906 and LC666907) were identical. Phylogenetic analysis revealed that the Bogor isolates clustered closely with M. multipori populations from China and Thailand, with high sequence homology of 99.30% and 99.10%, respectively. Morphological observations of the adult female specimens further confirmed their identity as M. multipori, based on key diagnostic features including body size, antennal segmentation, cerarii pattern, and distribution of pores and ducts, which correspond to descriptions in established taxonomic keys. This study provides the first molecular characterization of M. multipori in Indonesia. The COI sequence data obtained enhances reference databases for DNA barcoding and strengthens early detection strategies for pest monitoring. These findings are crucial for supporting quarantine inspections, management, and control of M. multipori in black pepper nurseries and preventing its spread to other crops.